Financial Data as a Mirror of an Economic Story. An Empirical Approach to the Impact of the COVID19 Pandemic on the Financial Equilibrium - Simona NICOLAE; George-Eduard GRIGORE; Radu-Cristian MUȘETESCU (European Journal of Interdisciplinary Studies)
The present article aims to analyze how the imbalances generated by the economic and medical crisis caused by the COVID 19 pandemic in 2020 were reflected in the balance and economic performance at the microeconomic level. Two companies operating in two of the most affected economic areas in 2020, Tourism and Pharmaceutical Industry, represented the foundation of our analysis. Accounting data from the Balance Sheet and Profit and Loss Account, available on the website of the Bucharest Stock Exchange, were the main tools for analyzing the impact that the economic and medical crisis had on indicators such as Working Capital, Self-financing Capacity, Current Ratio, Debt/Equity Ratio, Return on Assets, Return on Equity, etc. The period under consideration covers a period of 4 years, i.e., 2018-2021. The two areas of activity represent, in our opinion, two major poles of the effects of the COVID 19 pandemic, being the loser and the winner (in financial terms) of the economic and medical developments generated by these. The questions we propose to answer based on the financial analysis are: could these two companies also be considered the winner and the loser of 2020 crisis? And what is the story told by the financial data about a company's vulnerability during the crisis?